Efficacy and Safety of Primary Glaucoma Device Implantation Surgery in Exfoliative Glaucoma: A Retrospective Consecutive Case Series - Sang Yoong Park; Sang Wook Jin (Journal of Ophthalmology)
Purpose. To evaluate the efficacy and safety of primary glaucoma drainage implant (GDI) surgery for exfoliation glaucoma (XFG). Methods. This study was a retrospective, consecutive case series study including 36 eyes of 36 patients with XFG who underwent primary GDI surgery. Intraocular pressure (IOP), the mean deviation (MD) from the visual field exam, corneal endothelial cell density (ECD), and the number of topical antiglaucoma agents used during the preoperative and postoperative periods were retrospectively analyzed. Surgical success was defined by the following criteria: (1) IOP ≤ 18 mmHg and an IOP reduction of 20% with 1 or no medication; (2) IOP ≤ 15 mmHg and an IOP reduction of 25% with 1 or no medication; and (3) IOP ≤ 12 mmHg and an IOP reduction of 30% with 1 or no medication. The probability of success of GDI surgery was determined via Kaplan–Meier survival analysis. Results. The preoperative IOP was 25.9 ± 4.7 mmHg, and the postoperative IOP at 24 months was decreased to 14.2 ± 3.6 mmHg (p value < 0.001). The postoperative MD and ECD were similar to baseline (MD p value = 0.155; ECD p value = 0.055). However, a significant reduction in the number of antiglaucoma agents was observed (p value < 0.001). The surgical success rates were 77.8%, 63.9%, and 55.6% at 24 months for criteria 1, 2, and 3, respectively. Early hypotony (4 patients, 11.1%) and persistent corneal edema (5 patients, 13.9%) were the most common early and late postoperative complications, respectively. Conclusions. In XFG, primary GDI surgery reduced IOP by 45.2% and had a 77.8% success rate according to criteria 1 at 24 months postoperatively. However, considering that ECD reduction continues to decline over time, primary GDI surgery should be carefully considered in XFG.